Evaporation of water droplets under the enhanced gas concentration surrounding - Tan, Gary Zhao Quan (2015)
The evaporation of water droplet is a fundamental yet complex process in our nature after taking in all physical considerations. The study is beneficial in many industrial applications such as microelectronics, ink jet printing, cooling systems etc. Till today, the whole process of evaporation of a droplet has yet to be well understood in the academic world. The accumulated change of carbon dioxide results in a non-uniform water evaporation and condensation in our environment. In a previous study on a steady-state evaporation of water droplets, the interfacial liquid and vapor temperature were found to be not the same. Convection at the droplet interface also affected evaporation. Hence in the present study, a steady-state evaporation experiment will be extended to the evaporation of sessile water droplet under the controlled conditions including gas concentration, pressure and temperature.In the early stages of the project, a detailed literature review on the theory and experimental techniques of droplet evaporation were studied for a better understanding of the project’s field of study. Following that, substantial amount of time was invested into fabrication and setting up of the experimental rig. Lastly, a series of evaporation experiments were conducted by varying the pressure in the vacuum chamber or substrate temperature while maintaining the other factor constant at any one time in nitrogen filled conditions. The data collected was analyzed and verified by the Statistical Rate Theory (SRT). Based on the data collected from the experiments, it may be concluded that there was observable temperature non-uniformity between the vapor phase temperature and liquid phase temperature of an evaporating droplet along its vertical axis at any point of the droplet. The temperatures at the apex of the droplet in the liquid phase were also found to be higher than what was measured at the point close to the contact line. The relative humidity calculated based on the predicted vapor pressure computed with the SRT approach appears to support the experimental data gathered. Future works aims to explore this area of study with the use of a variety of surrounding gases, pressure levels and substrate temperatures.